2022
DOI: 10.53444/deubefd.1010921
|View full text |Cite
|
Sign up to set email alerts
|

Okullardaki Dağıtımcı Liderlik ile Sinerjik İklim Arasındaki İlişki

Abstract: Bu araştırma okullarda dağıtımcı liderlik ile sinerjik iklim arasındaki ilişkiyi belirlemek amacıyla gerçekleştirilmiştir. Araştırma ilişkisel tarama modelinde desenlenmiştir. Araştırmanın evrenini; 2020-2021 eğitim-öğretim yılında Adıyaman ili merkez ilçesinde bulunan devlete ait ilkokul, ortaokul ve liselerde görev yapan 4.445 öğretmen oluşturmaktadır. Örneklem ise seçkisiz örnekleme yöntemlerinden tabakalı örnekleme yöntemi kullanılarak oluşturulmuş olan 677 öğretmenden oluşmaktadır. Araştırma verilerinin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In his research, Şahin (2020) stated that transformational leadership, which is one of the leadership styles demonstrated by school principals, predicts school happiness to be 36%, while a similar research was stated by Arslan (2021) that servant leadership, which is one of the leadership styles demonstrated by school principals, predicts teachers' perceptions of organisational happiness to be 65%. In the research conducted by Sevim (2021), it is concluded that distributive leadership, one of the leadership styles demonstrated by school principals, predicted teachers' perceptions of organisational happiness to be 68%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his research, Şahin (2020) stated that transformational leadership, which is one of the leadership styles demonstrated by school principals, predicts school happiness to be 36%, while a similar research was stated by Arslan (2021) that servant leadership, which is one of the leadership styles demonstrated by school principals, predicts teachers' perceptions of organisational happiness to be 65%. In the research conducted by Sevim (2021), it is concluded that distributive leadership, one of the leadership styles demonstrated by school principals, predicted teachers' perceptions of organisational happiness to be 68%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When the domestic literature is examined, it is seen that the researches on the concept of organisational happiness conducted in recent years is limited. Although the organisational happiness variable was examined by the researchers with the following variables, it is seen that there is no research examining the relationship between the leadership styles of the school principals and the organisational happiness levels: organisational happiness perception (Bulut, 2015), differences management (Arslan, 2018), organisational silence (Moçoşoğlu & Kaya, 2018), organisational commitment (Demircan, 2019;İncekara, 2020), organisational cynicism and organisational justice (Korkut, 2019), organisational justice (Çetin, 2019), instructional leadership (Kuvvet, 2019), trust in administrators (Kotaoğlu, 2019), DNA profiles of schools (Köse, 2020), organisational trust (Gürbüz, 2020), organisational forgiveness (Bayram, 2020), managerial style (Bulut, 2020), motivating language (Ergüven, 2020), organisational justice and authentic leadership perceptions (Demir, 2020), occupational professionalism (Karnak, 2020), psychological empowerment (Özcocak & Yılmaz, 2020), readiness for organisational change (Sevim, 2021), teacher autonomy (Pazar, 2021), quality of work life (Elmas, 2021), servant leadership (Arslan, 2021) and psychological strength (Güzel, 2021). This research is important in terms of revealing the effect of the leadership styles of school principals, who are the administrators of schools, in ensuring organisational happiness in schools.…”
Section: Introductionmentioning
confidence: 99%